Life sentence - Gray, Lisa M.; Sound Mind Productions; Filmakers Library, inc. ([New York, NY] : Sound Mind Productions : Filmakers Library, [distributor], 2008)
Six incarcerated men and women, some of whom were sentenced as adolescents, prepare for their first parole board hearing. Each is denied and must wait two years until their next hearing, spending a total of 12 to 26 years in prison. They discuss what brought them to prison, the time spent there, and what being sentenced to decades of imprisonment felt like. Just before Congress abolished federal financing for college programs in prisons in 1994, all six had completed associate, bachelor, and master degrees. Later released, these longtermers contribute to society and their communities, all of them working with other formerly incarcerated people. The film shows the potential of people if they are given access to education and prepared for careers. Scholars, policy makers, and advocates of reform discuss the obstacles formerly incarcerated people face, including regulations, discrimination, sentencing policies, and lifetime parole.
DVD
Keywords: Ex-convicts -- Interviews; Ex-convicts -- Rehabilitation; Prison sentences -- New York (State); Prisoners -- Education -- New York (State)